Constructing a representative sample of out-of-care HIV patients from a representative sample of in-care patients. (October 2016) - Xia, Qiang; Neaigus, Alan; Bernard, Marie A; Raj-Singh, Shavvy; Shepard, Colin W
Individuals infected with HIV who are out of care are at a higher risk of HIV-related morbidity and mortality. It has been difficult to recruit a representative sample of out-of-care patients for epidemiological studies. Using a novel weighting method, we constructed a representative sample of out-of-care HIV patients from a representative sample of in-care patients. In-care patients were weighted based on the probability of receiving care during the study period and the probability of selection to participate in the study, and out-of-care patients were represented by those who were previously out of care and recently returned. The method can be used in other patient populations, if every patient in the population has a known, non-zero probability of receiving care and a known, non-zero probability of participating in the study.